Congenital Spigelian hernia in a neonate associated with several anomalies: A case report - Sinacer, Samira; Semari, Bilal Zakaria; Khemari, Soumia; Kharchi, Ahlem; Haif, Assia; Soualili, Zineddine (Journal of Neonatal Surgery, 2021)
Background: Spigelian hernia (SH) is a rare entity characterized by a defect of the anterior abdominal wall located along the Spigelian line, it may be congenital or acquired.Association with other anomalies is worth reporting. Case Presentation: A 22-day-old male newborn was admitted with strangulated right inguinal hernia and operated on emergently. Clinical examination also revealed a Spigelian hernia in the left lower abdominal quadrant with bilateral cryptorchidism, associated with polydactyly of the small right finger and anal stenosis. At surgery, the SH contained a part of the small intestine and the ipsilateral undescended testis. Conclusion: Pediatric SH is rare, but its association with undescended ipsilateral testis is frequent. Other abnormalities can be concomitant to this association.